2020
DOI: 10.14198/jhse.2021.164.07
|View full text |Cite
|
Sign up to set email alerts
|

Fan’s perspective on professional leagues and sporting events during COVID-19 confinement period

Abstract: The restriction imposed by COVID-19 pandemic has caused a great social change in the world and has affected many sectors, including the sport industry by having an impact and altering the normal development of the sport competitions and events. Therefore, it is fundamental to know sport fans' opinions about the professional championships during the confinement period. The sample is composed by 1025 professional sports leagues fans and major sporting events celebrated in Spain, with people in the age range 18-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Other studies that have evaluated the level of safety of the population towards participation in PA in Spain, showed that sports fans would not attend professional leagues or sports events as spectators without prevention measures that respect social distancing and the existence of a COVID-19 vaccine [ 39 ]. These authors highlighted that the young population had less uncertainty to attend as spectators, however, they maintained interest in watching television broadcasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies that have evaluated the level of safety of the population towards participation in PA in Spain, showed that sports fans would not attend professional leagues or sports events as spectators without prevention measures that respect social distancing and the existence of a COVID-19 vaccine [ 39 ]. These authors highlighted that the young population had less uncertainty to attend as spectators, however, they maintained interest in watching television broadcasts.…”
Section: Discussionmentioning
confidence: 99%
“…The group of participants at addiction risk showed a high percentage of running or cycling activities in the home during the lockdown period compared to the other two groups. Marques et al [ 39 ], indicated that the Brazilian population increased the practice of activities related to conditioning by 8.7%, walking or running increased by 7.4% and functional training increased by 44.9% during lockdown. Schwendinger and Pocecco [ 61 ] indicated that an ideal activity to perform at home may be functional training, due to the short duration of intervals and minimal use of equipment.…”
Section: Discussionmentioning
confidence: 99%
“…The sports industry suddenly stopped all events. The COVID-19 outbreak that started in mid-December 2019 in Wuhan (China) had already infected more than 3.2 million people in the world in early May 2020 (Jose Miguel et al 2020). Many countries around the world had to impose restrictive measures which had affected thousands of million people due to the high rate of propagation and contagion as well as to the difficulty to control it.…”
Section: Introductionmentioning
confidence: 99%
“…In this crisis situation, researchers from around the world are sharing information about professional sport and spectators during the COVID-19 pandemic, such as economic impact (Bond et al, 2020;Drewes et al, 2021), the influence of absent in-stadium spectators for professional sport clubs (Herold et al, 2021), the example of volleyball club experiences (Piatti et al, 2021), stadium attendance demand , public perceptions of sport events (Sato et al, 2020), and fans' perspectives on professional leagues and sport events (Vegara-Ferri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to Vegara-Ferri et al (2020), more than 50% of fans strongly missed watching matches, although more than 50% of fans did not feel safe attending leagues and events. They also report Advance Publication by J-STAGE Published online October 14, 2021 differences in each item by age group.…”
Section: Introductionmentioning
confidence: 99%